Gestão de custos no setor público: análise da viabilidade de implantação do sistema de informações de custo do Governo Federal (SIC) no Instituto Federal de Educação, Ciência e Tecnologia da Paraíba (IFPB) - Costa Júnior, Fernando Torres da (2016)
This work had as main objective to conduct an analysis of the current accounting system / Finance of the Federal Institute of Paraiba - IFPB with a view to implementation of the proposal and / or operation of the Cost Information System of the Federal Government - SIC - in IFPB . The SIC is an important tool of management accounting, with a view to its implementation, currently the reality of the public sector, aims to support public management regarding the planning and control of decision-making; demonstrating the potential benefits of public accounting activity and cost accounting within the public, whether in the macro budget process and / or financial; contributing to improving the quality of public expenditure management. The dissertation provides an overview of the challenges to effective implementation of the Cost Information System of the Federal Government, which to be developed, it will need some procedures such as the standardization of accounting entries, which will prevent the loss of comparability attribute; the change in the balance control system and the creation of a model unit on cost system, later to be expanded to campuses IFPB. The goal was to improve the decision-making processes in IFPB as cultural change challenge in the public organization in favor of measuring the cost of the goods and services and the importance of SIC as allocative improvement element for efficiency, effectiveness and effectiveness in public expenditure management.